Specific Criminal Profiling and Interrogation Techniques as Forensic Psychology Methods in Hungarian Law Enforcement - Erdélyi, Ákos (Magyar Rendészet, 2023)
One of the applied areas of criminal psychology, the forensic psychology presents how the knowledge of psychology can be applied in the most optimal way in order to effectively detect individual crimes. A trend has appeared in law enforcement agencies for psychologists to carry out special activities in the criminal field. One specific activity is criminal profiling and the other is the development of the most effective interrogation techniques. Now I attempt to present these two specific criminal tasks of psychology. I present a literature review on how forensic psychology can be used during profiling and the planning of special interrogations. Despite the fact that offender profiling is not new for law enforcement agencies, its clinical trend has begun to appear and spread independently in recent years. The application of psychology in the planning of individual interrogations is a much more researched field and used during weekday work.